Mechanism of the DL-alpha-aminoadipic acid inhibitory effect on form-deprived myopia in guinea pig - Mao, Jun-Feng (International Journal of Ophthalmology Press, 2013)
AIM: To investigate the effect of intravitreal injection of DL-alpha-aminoadipic acid (DL-α-AAA) on ocular refractive state and retinal dopamine, transforming growth factor-β(2) (TGFβ(2)), vasoactive intestinal polypeptide (VIP) in guinea pig form-deprived myopia. METHODS: Four-week-old pigmented guinea pigs were randomly assigned to 4 groups: normal control, deprivation, deprivation plus DL-α-AAA, deprivation plus saline. Form deprivation was induced with the self-made translucent eye shields, and lasted for 14 days. 8µg DL-α-AAA was injected into the vitreous chamber of deprived eyes. The corneal radius of curvature, refraction and axial length were measured. Retinal dopamine content was evaluated by the high-performance liquid chromatography with electrochemical detection, and TGFβ(2) and VIP protein were detected by Western blotting. RESULTS: Fourteen days of eye occlusion caused the axial length to elongate and become myopic in the form-deprived eyes, with the decrease of retinal dopamine and the increase of TGFβ(2) and vasoactive intestinal polypeptide (VIP) protein. Intravitreal injection of DL-α-AAA could inhibit the myopic shift from (-3.65±1.06)D to (-1.48±0.63)D, P<0.01 due to goggles occluding and cause the decrease of retinal TGFβ(2) protein in the deprived eyes. However, intravitreal injection of DL-α-AAA had no significant effect on retinal dopamine and VIP protein in deprived eyes. Retinal TGFβ(2) protein correlated highly with the ocular refraction (y=-3.34+0.31/x, F=74.75, P<0.001) and axial length (y=8.39-0.02/x, F=48.32, P<0.001) in different treatment groups. CONCLUSION: Intravitreal injection of DL-α-AAA is effectively able to suppress the development of form deprivation myopia, which may be associated with retinal TGFβ(2) protein in guinea pigs.